Strength properties of high volumes of slag concrete for rigid pavements - Vijaya Gowri, T; Sravana, P; Srinivasa Rao, P; Chandrasekhar Rao, T (International Journal of Engineering and Technology, 2018)
Concrete is one of the most versatile materials used in the construction industry in which cement is used as main ingredient playing a dominant role in gaining of strength. Despite of it, the production of cement leads to depreciation of natural materials. Regarding this aspect, in this study an attempt has been made to use GGBS (Ground Granulated Blast Furnace Slag) as a substitute material to cement with a percentage replacement of 50% .Specimens with various geometric shapes like cubes, cylinders and prisms were casted and tested with(High Volume Slag Concrete) and without replacements of GGBS, varying water-cement ratios of 0.55, 0.45, 0.36 & 0.27 for mechanical properties, Youngâ€™s Modulus of elasticity, impact strength with and without the addition of steel fibers and also abrasion resistance after 28 days and 90 days of curing.Â Â